Post Harvest Practices among the Muna Ethnic Group: A Literature Review on Local Wisdom in Sustainable Agriculture - La Panga (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2025)
Post-harvest practices are a critical phase in the agricultural production system, directly affecting the quality, quantity, and market value of harvested crops. In Indonesia, particularly among indigenous communities such as the Muna ethnic group in Southeast Sulawesi, post-harvest activities are still conducted using traditional methods passed down through generations. This literature review aims to identify, analyze, and evaluate the traditional post-harvest practices of the Muna people and assess their relevance within the framework of sustainable agriculture. The study draws upon scientific publications, ethnographic records, and research reports related to traditional farming systems and local wisdom in the Muna region. The findings reveal that practices such as bamboo granary storage (tambu), sun-drying methods, and crop bartering systems carry ecological, social, and economic values that align with the principles of sustainable agriculture. Despite the advancement of modern technologies, these indigenous practices remain relevant as they contribute to environmental conservation, strengthen local food security, and preserve cultural heritage. This study recommends integrating these traditional practices into sustainable agricultural development programs grounded in local wisdom.